Implementation of Criminal Sanctions Against Perpetrators of Theft Crimes Based on Legal Certainty (Case Study of Decision Number 144/Pid.B/2024/PN.Smg - Fitriani, Riska; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. The case study in this research is Decision Number 144/Pid.B/2024/PN Smg. By considering Article 362 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations, the court declares that the Defendant Rilly Pradana Purnama Putra Bin Slamet Bowo Mulyono has been proven legally and convincingly guilty of committing the crime of